1971
DOI: 10.1113/jphysiol.1971.sp009473
|View full text |Cite
|
Sign up to set email alerts
|

An electrical description of the motoneurone, and its application to the analysis of synaptic potentials

Abstract: SUMMARY1. The Rall model of the motoneurone, which consists of a lumped resistance and capacitance, representing the soma, in parallel with a distributed resistance-capacitance network of finite length, representing the equivalent dendritic cable, has been used to investigate the effects of varying electrical and geometrical parameters on the time course of transients generated at the model soma.2. An analytical solution has been obtained for the voltage at the model soma, following a brief current injection a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

1974
1974
1992
1992

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(59 citation statements)
references
References 21 publications
2
57
0
Order By: Relevance
“…amplitudes compatible with the estimated value of the time integral of a quantal conductance change, 40 x 10-10 mho msec (see Methods). Peak amplitude values corresponding to quantal conductance pulses in the physiological range of 0-2-0-5 msec are enclosed within vertical lines (see Methods; Kuno & Miyahara, 1969a;Jack & Redman, 1971b). Thus a quantal conductance change at the distal dendritic site illustrated here would be expected to generate an e.p.s.p.…”
Section: Resultsmentioning
confidence: 99%
“…amplitudes compatible with the estimated value of the time integral of a quantal conductance change, 40 x 10-10 mho msec (see Methods). Peak amplitude values corresponding to quantal conductance pulses in the physiological range of 0-2-0-5 msec are enclosed within vertical lines (see Methods; Kuno & Miyahara, 1969a;Jack & Redman, 1971b). Thus a quantal conductance change at the distal dendritic site illustrated here would be expected to generate an e.p.s.p.…”
Section: Resultsmentioning
confidence: 99%
“…A shift in the apparent reversal potential to levels more negative than the true equilibrium potential and a 'shunting' of the dendritic conductance change are qualitatively consistent with dendritic synaptic locations (Rall, 1967;Smith, Wuerker & Frank, 1967;Jack, Noble & Tsien, 1975). Computational experiments, making use of a compartmental model (Rall, 1964(Rall, , 1967Jack & Redman, 1971), showed that the observed shift in the slow e.p.s.p. reversal potential is also quantitatively compatible with the observed discrepancy in the conductance ratios (J.…”
Section: Discussionmentioning
confidence: 99%
“…As the initial faster decay did not last for longer than 10 % of the final cell time constant, the cell dendrites must be electrically short, i.e. less than 0 5 space constants (Jack & Redman, 1971; see also McLachlan, 1974). The proportion of cells whose electrotonic potentials gave evidence of dendritic current spread increased during the developmental period examined.…”
Section: Anatomical Observationsmentioning
confidence: 99%